Rising to the occasion? Youth political knowledge and the voting age - Olof Rosenqvist (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2016)
Voting is a fundamental human right. Yet, individuals that are younger than 18 do typically not have this right since they are considered uninformed. However, recent evidence tentatively suggests that the political knowledge of youths is endogenous to the voting age. I test for the existence of such dynamic adjustments utilizing voting age discontinuities caused by Swedish laws. I employ a regression discontinuity strategy on Swedish register data to estimate the causal effect of early age voting right on political knowledge around age 18. The results do not support the existence of positive causal effects of early age voting right on political knowledge. Thus, we should not expect that 16-year-olds respond by acquiring more political knowledge if they are given the right to vote. This finding weakens the case for a lowering of the voting age from 18 to 16.
Keywords: I21; P16; D04; D72; I29; 330; voting age; political knowledge; civic interest; tertiary education; regression discontinuity design